Electrophysiology of executive control in spoken noun-phrase production: Dynamics of updating, inhibiting, and shifting. (April 2016) - Sikora, Katarzyna; Roelofs, Ardi; Hermans, Daan
Abstract: Previous studies have provided evidence that updating, inhibiting, and shifting abilities underlying executive control determine response time (RT) in language production. However, little is known about their electrophysiological basis and dynamics. In the present electroencephalography study, we assessed noun-phrase production using picture description and a picture-word interference paradigm. We measured picture description RTs to assess length, distractor, and switch effects, which have been related to the updating, inhibiting, and shifting abilities. In addition, we measured event-related brain potentials (ERPs). Previous research has suggested that inhibiting and shifting are associated with anterior and posterior N200 subcomponents, respectively, and updating with the P300. We obtained length, distractor, and switch effects in the RTs, and an interaction between length and switch. There was a widely distributed switch effect in the N200, an interaction of length and midline site in the N200, and a length effect in the P300, whereas distractor did not yield any ERP modulation. Moreover, length and switch interacted in the posterior N200. We argue that these results provide electrophysiological evidence that inhibiting and shifting of task set occur before updating in phrase planning. Highlights: We used EEG to examine the dynamics of executive control in language production. We examined updating, inhibiting, and shifting in noun-phrase production. Production latencies revealed updating, inhibiting, and shifting effects. We found N200 effects for inhibiting and shifting and a P300 effect for updating. Inhibiting and shifting of task set precede updating in phrase planning.